Interprofessional health education in Australia: Three research projects informing curriculum renewal and development - Steketee, C.; Forman, Dawn; Dunston, R.; Yassine, T.; Matthews, L.; Saunders, R.; Nicol, P.; Alliex, S. (Elsevier Science, 2014)
Purpose: This paper reports on three interrelated Australian studies that provide a nationally coherent and evidence-informed approach to interprofessional education (IPE). Based on findings from previous studies that IPE tends to be marginalized in mainstream health curriculum, the three studies aspired to produce a range of resources that would guide the sustainable implementation of IPE across the Australian higher education sector. Method: Nine national universities, two peak industry bodies and a non-government organization constituted the study team. Data were gathered via a mixture of stakeholder consultations, surveys and interviews and analyzed using quantitative and qualitative methods. Results & Conclusion: An important outcome was a curriculum renewal framework which has been used to explore the implications of the study's findings on Australian nursing. While the findings are pertinent to all health professions, nursing is well placed to take a leading role in establishing IPE as a central element of health professional education.